New quality assurance program integrating “modern radiotherapy” within the German Hodgkin Study Group - Kriz, Jan; Herfarth, Klaus (Strahlentherapie und Onkologie, 2017)
Introduction: Field design changed substantially from extended-field RT (EF-RT) to involved-field RT (IF-RT) and now to involved-node RT (IN-RT) and involved-site RT (IS-RT) as well as treatment techniques in radiotherapy (RT) of Hodgkin’s lymphoma (HL). The purpose of this article is to demonstrate the establishment of a quality assurance program (QAP) including modern RT techniques and field designs within the German Hodgkin Study Group (GHSG).Methods: In the era of modern conformal RT, this QAP had to be fundamentally adapted and a new evaluation process has been intensively discussed by the radiotherapeutic expert panel of the GHSG. Results: The expert panel developed guidelines and criteria to analyse “modern” field designs and treatment techniques. This work is based on a dataset of 11 patients treated within the sixth study generation (HD16-17). Conclusion: To develop a QAP of “modern RT”, the expert panel defined criteria for analysing current RT procedures. The consensus of a modified QAP in ongoing and future trials is presented. With this schedule, the QAP of the GHSG could serve as a model for other study groups.